The Paralysing Sea: A Cognitive Analysis of the Discourse Worlds in James Joyce’s “Eveline” (TEST Ticontre. Theory Text Translation, 2022)
The hypothesis underpinning the present essay is that, in James Joyce’s «Eveline», wish worlds, speculative extensions and intention worlds allow the protagonist to mentally escape her reality; explore new dimensions, and awake a desire to change her current condition. The above-mentioned worlds are strictly bound to the sea, both seen as a limit and a possibility. The short story is scattered with images related to water that, if combined with the analysis of the discourse worlds and the cognitive phenomenon of isolation realised through epiphanies, could lead to a deeper and far-reaching understanding of the literary work object of the present study. In conclusion, this essay aims to analyse the relationship between Eveline’s discourse worlds and the sea, focusing on the epiphanies since they can be considered a bridge between the inner selves and the external world, often provoking a reciprocal change.